High-throughput phenotyping of multicellular organisms: finding the link between genotype and phenotype - Sozzani, Rosangela (BioMed Central, 2011)
High-throughput phenotyping approaches (phenomics) are being combined with genome-wide genetic screens to identify alterations in phenotype that result from gene inactivation. Here we highlight promising technologies for 'phenome-scale' analyses in multicellular organisms.